(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study, titled " An Analytical Study of Cross-Examination Dynamics and its Impact on the Justice Delivery System," delves into the critical role of cross-examination in the judicial process. Focusing on civil and criminal trials, the research explores the intricate balance between witness examination and the quest for justice. It scrutinizes the procedural reforms, such as the introduction of affidavits for evidence-in-chief and the consequent challenges in civil courts. The study further examines the impact of piecemeal cross-examination, witness demeanor assessment, and the judicial discretion in handling objections and re-examinations. By analyzing key rulings and legal precedents, this research highlights the complexities and nuances of cross-examination, emphasizing its importance in the effective functioning of the justice delivery system. The study aims to provide a comprehensive understanding of cross-examination practices, identify areas needing reform, and suggest measures to optimize the process for quicker and fairer trial outcomes.